Direct development of stem tetrapods across the fin-to-limb transition - Jason D. Pardo; Arjan Mann (Science, 2026)
Modern amphibians are characterized by an aquatic larval stage that ends abruptly with a period of widespread tissue remodeling (metamorphosis) upon transition to terrestrial adulthood. A transient larval stage ending in gradual metamorphosis is often assumed for the earliest digited tetrapods, but direct evidence of this larval stage is lacking. Exceptionally preserved stem tetrapod hatchlings show that a transient larval stage was absent in tetrapods both before and after the fin-to-limb transition; instead we identified soft- and hard-tissue evidence of direct development, falsifying hypotheses of an ancestral origin of metamorphosis or of a gradual larval-postlarval transition serving as a template for lissamphibian metamorphosis. We argue that a transient larval period culminating in metamorphosis originated near or within the tetrapod crown group as part of a broader suite of traits associated with terrestrialization.